Agency as power: An ecological exploration of an emerging language teacher leaders’ emotional changes in an educational reform - Gao, Yuan; Cui, Yaqiong (Frontiers in Psychology, 2022)
Teacher emotion, an important aspect in Language Teacher Psychology (LTP), has recently drawn growing attention in language teacher development studies. Previous research has shown that language teachers, typically pressured by heavy workloads, may face multiplied sources of emotional challenges, especially in the context of educational change such as curriculum reform and the COVID-19 emergency. Current literature on teacher emotions largely centers around ordinary language teachers, with teacher leaders whose agentic actions often exert greater influence on the effectiveness of educational changes rarely examined. Situated in a top-tier research university which has been promoting an EAP reform to enhance its science students’ multilingual competence in academic contexts, this longitudinal case study tracked the emotional trajectory of an English teacher Lea for 5 years. Based on Bronfenbrenner’s (2005) ecological perspective, our study confirms that language teachers’ emotions vary across the reform ecosystems and extends the current inquiry by conceptualizing the intricately interrelated teacher emotion, agency, power, and identity as dynamic constructs. This study also reveals how the reform-inflected emotional changes were associated with Lea’s EAP teacher and teacher leader identity construction, with both identities reinforcing each other, which to some extent reconciled Lea’s emotional tensions. Our study bears significant implications for language teachers involved in an educational reform, teacher leaders, and school administrators.